Rheo-optical Behaviors and Stability of a Silica Particle Suspension Coated with Silane Coupling Agents - Lee, Jae-Dong; Yang, Seung-Man (Journal of colloid and interface science, 1998)
The rheo-optical behaviors and suspension stability of silica particles coated with silane coupling agents were investigated experimentally. Mono-dispersed silica particles were synthesized by the sol–gel method and the particles were coated with silane coupling agents such as vinyltriethoxy silane (VTES) and γ-methacryloxypropyl triethoxy silane (MPTES). Although all the suspensions of identical particle volume fraction exhibited similar rheological behaviors at high shear rates, only the stabilized suspensions coated with either VTES or MPTES displayed smooth shear thinning rather than abrupt change in the shear viscosity, as is typical of suspensions with no surface treatment. The present study showed that the MPTES coating was very effective in enhancing the phase stability compared to the VTES coating. The flow-induced dichroism for the MPTES-coated suspensions did not experience sign change, while those of the non-stabilized suspensions changed sign as the shear rate was increased. The VTES-coated suspensions underwent a transition from a stable to an unstable state as the particle volume fraction increased. Specifically, the rheological behaviors of the VTES-coated suspensions of particle volume fraction 0.35 were similar to those of the MPTES-coated suspensions. When the volume fraction exceeded 0.45, however, the effect of VTES coating diminished. Finally, the stress-optical rule proposed by Bender and Wagner was adopted to model the stabilized suspensions considered here. The present results indicated that the stress-optical coefficient could be predicted successfully by the proposed stress-optical rule if the contribution from the hydrodynamic interaction is considered separately from the thermodynamic contribution.